Durable pulmonary vein isolation with diffuse posterior left atrial ablation using low‐flow, median power, short‐duration strategy. (5th June 2022) - Li, Dan L.; El‐Harasis, Majd; Montgomery, Jay A.; Richardson, Travis D.; Kanagasundram, Arvindh; Estrada, Juan Carlos; Lean, Michael; Shoemaker, M. Benjamin; Saavedra, Pablo J.; Touchton, Steven; Patel, Bindiya; Herrmann, Tarrah; et al.
Abstract: Introduction: To target posterior wall isolation (PWI) in atrial fibrillation (AF) ablation, diffuse ablation theoretically confers a lower risk of conduction recovery compared to box set. We sought to assess the safety and efficacy of diffuse PWI with low‐flow, medium‐power, and short‐duration (LF‐MPSD) ablation, and evaluate the durability of pulmonary vein isolation (PVI) and PWI among patients undergoing repeat ablations. Methods: We retrospectively studied patients undergoing LF‐MPSD ablation for AF (PVI + diffuse PWI) between August 2017 and December 2019. Clinical characteristics were collected. Kaplan‐Meier survival analysis was performed to study AF/atrial flutter (AFL) recurrence. Ablation data were analyzed in patients who underwent a repeat AF/AFL ablation. Results: Of the 463 patients undergoing LF‐MPSD AF ablation (PVI alone, or PVI + diffuse PWI), 137 patients had PVI + diffuse PWI. Acute PWI with complete electrocardiogram elimination was achieved in 134 (97.8%) patients. Among the 126 patients with consistent follow‐up, 38 (30.2%) patients had AF/AFL recurrence during a median duration of 14 months. Eighteen patients underwent a repeat AF/AFL ablation after PVI + diffuse PWI, and 16 (88.9%) patients had durable PVI, in contrast to 10 of 45 (23.9%) patients who had redo ablation after LF‐MPSD PVI alone. Seven patients (38.9%) had durable PWI, while 11 patients had partial electrical recovery at the posterior wall. The median percentage of area without electrical activity at the posterior wall was 70.7%. Conduction block across the posterior wall was maintained in 16 (88.9%) patients. Conclusion: There was a high rate of PVI durability in patients undergoing diffuse PWI and PVI. Partial posterior wall electrical recovery was common but conduction block across the posterior wall was maintained in most patients.